The Moral Degradation of Corruption Perpetrators from The Perspectives of Pancasila and Criminology - Laura Erika Hasibuan (Jurnal Hukum In Concreto, 2026)
Corruption committed by public officials in Indonesia is inseparable from the problem of moral degradation and the erosion of individual integrity. This study aims to examine the deviant behavior of corrupt actors from a criminological perspective and to analyze the role of Pancasila as a moral foundation in preventing the formation of criminal intent (mens rea) in acts of corruption. This research employs a normative juridical method with a conceptual and philosophical approach, analyzing legal norms, doctrines, and ideological values. The findings reveal that corruption is best understood as a form of white-collar crime, which is not driven by economic necessity but rather by greed and opportunity, as explained in the gone theory. Such behavior is learned and shaped through social interaction within permissive environments, as outlined in the differential association theory. On the other hand, the values of Pancasila, through containment theory, offer an internal mechanism of moral control known as inner containment that theoretically inhibits deviant actions. However, the weak internalization of Pancasila among public officials contributes to their failure to uphold ethical responsibilities in governance. This study concludes that corruption should be viewed not only as a legal crime but also as an ideological violation against the philosophical foundation of the Indonesian state. Therefore, anti-corruption strategies must combine legal enforcement with moral reconstruction grounded in state ideology.